Influence of acupuncture on the expression of VIP, SP, NKA and NKB, cAMP/cGMP and HE content and treatment of bronchial asthma in rats - Chen, Yujuan; Gao, Yanlu; Lu, Wenwen; Gao, Wei (Cellular and Molecular Biology, 2020)
This research was set up to explore the neural mechanisms of acupuncture in the treatment of bronchial asthma in rats by detecting the content of substance P(SP), vasoactive intestinal peptide (VIP), neurokinin A(NKA), neurokinin B (NKB), cyclic adenosine monophosphate/cyclic guanosine monophosphate ratio (cAMP/cGMP) and hematoxylin-eosin (HE) staining for the pathological changes of lung tissue, in order to Institute Certain Experimental and Theoretical Foundation for Traditional Chinese Medicine (TCM) Prevention and Treatment of Bronchial Asthma. For this purpose, fifty healthy adult Wistar male rats, weighing 200-250 g, were randomly divided into 5 groups: normal control group A, asthma control group B, asthma acupuncture group C, adrenalectomy (ADX)-asthma group D, adrenalectomy (ADX)-asthma acupuncture group E. Group A was raised with other groups at the same period; Group B was induced asthma by ovalbumin; Group C was induced asthma as Group B and then acupunctured five acupoints (bilateral Feishu, bilateral Fengmen, and Dazhui); Group D was induced asthma after adrenalectomy; group E was treated with acupuncture on the basis of group D. HE staining was performed in the lung tissue of rats from each group, and histopathologic changes were observed. SP, VIP, NKA, NKB in each rat lung tissue were measured by immunohistochemistry. cAMP/cGMP was measured with ELISA to speculate the neural mechanisms of acupuncture in the treatment of bronchial asthma. The results were as: decrease of cAMP/cGMP and VIP and increase of SP, NKA, NKB in the lung tissue are the neural mechanisms of an asthma attack. The increase of cAMP/cGMP and decrease of NKA, NKB, SP and VIP in the lung tissue of group C indicated the improvement of bronchial asthma symptoms. It is possible that the decrease of NKA and NKB, increase of cAMP/cGMP and a slight change of SP and VIP in group E were related to the reduction of glucocorticoid after ADX which influenced the effect of acupuncture. The neural regulation mechanisms of acupuncture in the treatment of bronchial asthma were related to bronchiectasis caused by stimulation of adrenergic nerve and inhibition of the vagus nerve function by acupuncture, and related to the release of inflammatory mediators.